Perceptions of financial institutions towards financing Public Private Partnership (PPP) projects in Malaysia - Abdullah Asuhaimi, Fadhilah; Ismail, Suhaiza (IIUM Press, 2013)
This chapter presents a study that explores the perceptions of financial institutions on several aspects of PPP implementation in Malaysia, which include the commitment towards PPP, the understanding of the PPP concept and the factors that determine the decision of the financial institutions to finance PPP projects in Malaysia. To achieve the objectives, a questionnaire survey method was used. The questionnaire was distributed to all financial institutions in Malaysia. Out of the 47 distributed questionnnaire (i.e., 47 financial institution) only 13 financial institutions responded, representing a response rate of 27.66%. The result reveal that the financial institutions have a high level of understanding of the PPP concept in Malaysia although they perceive that the current availability of PPP information is moderate. In addition, the study found that all the participating financial institutions except one are willing to finance PPP projects. In terms of factors that are considered by the financial institutions in offering finance to PPP projects, 'payback period of the projects' is recognised as the most important factor followed by 'government's guarantee', 'business relation with borrowers', 'environmental viability of the project', 'economic progress of the economy', 'national priority', 'collateral pledged by borrowers', 'social progress of the economy', and, lastly, ' political reasons'.